Meningkatkan Membaca Permulaan Melalui Metode Multisensori bagi Anak Kesulitan Belajar - Megga Wati; Damri Damri (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2019)
This research began with the problems which found at SDN 12 Pisang, the researcher distributed the reading instruments to the 3rd grade students in SDN 12 Pisang that consists of 29 students, then 4 children have been identified. The researcher choosed 1 child which the child has the experiences in the academic difficulties aspect. Then, the researcher ensured that by conducting interviews with their parents and assessing the child, so that the result was the child has a difficulty in academic aspects, especially Indonesian language. The child has identified that is difficult to read, especially in reading a text in double consonants. This study aims to prove whether the multisensory method is effective in improving the ability of the early reading in the children learning difficulties to the 3rd grade of SDN 12 Pisang. The study used an experimental approach in a Single Subject Research (SSR) form. This research used the AB design and the data analysis techniques used graphical visual analysis. Research subjects were the children with the learning difficulties. The target behavior in this study is the children who can read fluently. The variables measurement is by using a percentage of the number of items that can be done properly and correctly. The observation was done with three sessions. First, the baseline session (a) which was carried out in 4 observations for 35 minutes per percentage per meeting which obtained ranged from 20% to 25%. Second, intervention sessions through multysensory method (b) were carried out 6 times which the percentage of meeting obtained at the time of intervention was between 33% to 85%. The tendency of direction, the tendency for the stability, the tedency of data traceability and the level changes which have increased positively. Thus, it can be concluded that the multisensory method is effective in improving reading skills of learning difficulties’ children. Therefore, the teacher can apply multisensory methods to improve reading skills of learning difficulties’ children.